Synopsis Articles in the Planning of a Trilingual Dictionary: Yilumbu-French-English - Mavoungou, P.A. (Lexikos, 2002)
Abstract: A distinction is often drawn between single articles and synopsis articles. A single article is the so-called default article. It does not deviate from the traditional microstructural approach of the dictionary because it presents the minimum data for each lemma sign treated, while a synopsis article gives additional data for each treated lemma. The classical conception of the synopsis article originates with Bergenholtz, Tarp and Wiegand (1999). In their view, synopsis articles which were devised for language for special purposes (LSP) dictionaries have to make provision for the treatment of lemma signs functioning as superordinate terms (general lemmata or topics) as well as their hyponyms. The aim of this article is to present a new lexicographic approach to the study of synopsis articles against the background of a planned trilingual dictionary. It will be shown that synopsis articles have a more general use than its restricted application in LSP dictionaries. In fact, the focus will not be on the treatment of technical or scientific vocabulary but rather on cultural terms. This article also raises among other things, questions about the purpose of the planned dictionary, its target users, different types of microstructures as well as different data categories to be included in synopsis articles.Keywords: SYNOPSIS ARTICLE, SINGLE ARTICLE, DIFFERENT TYPES OF MICROSTRUCTURES, LEMMA SIGN, LINGUISTIC AND EXTRA-LINGUISTIC ASPECTS, LSP DICTIONARIES, TARGET GROUP, DATA CATEGORIES, CULTURE-BOUND LEXICAL ITEMS, SPECIALFIELD TERMSAbstract: Articles synopsis dans la planification d'un dictionnaire trilingue:yilumbu–français–anglais. Une distinction est souvent faite entre articles simples et articlessynopsis. L'article simple est encore connu sous la dénomination d'article par défaut. Il nedévie pas de l'approche microstructurelle traditionnelle du dictionnaire parce qu'il présente leminimum pour chaque lemme traité, alors qu'un article synopsis offre des données additives pourchaque lemme traité. La conception classique d'article synopsis est de Bergenholtz, Tarp et Wiegand(1999). De leur point de vue pour les articles synopsis qui ont été conçus pour des dictionnairesde langue de spécialité (LSP), des dispositions doivent être prises pour le traitement de signeslemmesfonctionnant comme termes superordonnés (lemmes généraux ou thèmes) ainsi que leurshyponymes. L'objectif de cet article est de présenter une approche lexicographique nouvelle pourl'étude des articles synopsis avec en toile de fond un dictionnaire trilingue en proposition. Il seramontré que les articles synopsis ont un usage plus large que leur application limitée aux dictionnairesLSP. En effet, le centre d'intérêt portera non pas sur le traitement des termes du vocabulaire technique ou scientifique mais plutôt sur des termes culturels. Cet article soulève également entreautres choses des interrogations quant à la visée du dictionnaire proposé, ses utilisateurs cibles, lesdifférents types de microstructures ainsi que les différentes catégories de données à inclure pourchaque article synopsis.Mots-clés: ARTICLE SYNOPSIS, ARTICLE SIMPLE, DIFFÉRENTS TYPES DE MICROSTRUCTURES,SIGNE-LEMME, ASPECTS LINGUISTIQUES ET EXTRA-LINGUISTIQUES, DICTIONNAIRESLSP, GROUPE CIBLE, CATÉGORIES DE DONNÉES, ITEMS LEXICAUX CENTRÉS SURLA CULTURE, TERMES TECHNIQUES